Hippocampal damage and atrophy secondary to status epilepticus in a patient with schizophrenia - Fujisao, Elaine K.; Cristaldo, Nathalia R.; Braga, Aline M.; Cunha, Paulina R.; Yamashita, Seizo; Betting, Luiz Eduardo (Frontiers in Neurology, 2017)
A 59-year-old man was admitted with respiratory tract infection, compromised conscience and generalized tonic-clonic seizures. His medical history included schizophrenia diagnosis, for which he had been being treated since he was 27 years old. EEG disclosed non-convulsive status epileptics. An MRI acquired 3 days later showed increased left hippocampal volume with hyperintensity on T2-weighted and FLAIR sequences. After being treated with antibiotics and antiepileptic medications, the patient’s condition improved. A follow-up MRI showed reduction of the left hippocampus. The relationship between epilepsy and schizophrenia is not yet clear. This case illustrates this interaction. Hippocampal atrophy may have been caused by environmental aggression in the present patient with schizophrenia, perhaps in association with a predisposing genotype.